Hydrothermal formation of N/Ti3+ codoped multiphasic (brookite–anatase–rutile) TiO2 heterojunctions with enhanced visible light driven photocatalytic performance. Issue 45 (2nd November 2017) - Sun, Mingxuan; Kong, Yuanyuan; Fang, Yalin; Sood, Swati; Yao, Yuan; Shi, Jifeng; Umar, Ahmad
Abstract : Multiphasic TiO2 heterojunctions codoped with N and Ti 3+ were fabricated and their enhanced visible light photocatalytic activity for the degradation of methylene blue was demonstrated. Abstract : Mixed phased TiO2 catalysts codoped with N and Ti 3+ have been successfully synthesized using a low-temperature, one step hydrothermal method using TiN as the precursor. The as prepared samples were studied for their crystalline structure, morphology, composition, and optical properties using various analytical techniques such as X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS), and X-ray photoelectron spectroscopy (XPS). It was observed that N and Ti 3+ codoped TiO2 samples having mixed phases of brookite, anatase and rutile could be obtained at a wide range of hydrothermal time durations ranging from 24 h to 72 h. The as-prepared samples exhibit a distinct red shift, suggesting that N and Ti 3+ codoping significantly enhances the optical absorption characteristics of TiO2 . The photocatalytic activity of the prepared samples was studied using methylene blue and colorless resorcinol dyes. The prepared samples demonstrated good photocatalytic activity because of their excellent mixed phase crystalline structures and an increase in the threshold wavelength response. The mechanism of the photocatalytic degradation reaction was also studied. This work provides a novel strategy to fabricate and extend the visible light response of TiO2, which facilitates their application in the environment remediation and energy conversion.